Prevention and amelioration of collagen-induced arthritis by blockade of the CD28 co-stimulatory pathway: requirement for both B7-1 and B7-2. - Webb, L; Walmsley, M; Feldmann, M (1996)
Collagen type II-induced arthritis (CIA) is an experimental model of arthritis that has been successfully used to dissect the pathogenesis of human rheumatoid arthritis and to identify potential therapeutic targets. We have used this model to evaluate the role of T cell co-stimulation in both disease development and progression. T cell co-stimulation is provided by ligation of CD28 with either B7-1 or B7-2 present on antigen-presenting cells and can be prevented by a soluble form of CTLA-4 (CTLA-4Ig) which binds with high affinity to both B7-1 and B7-2. We found that administration of CTLA-4Ig at the time of immunization prevented the development of CIA and was associated with lack of lymphocyte expansion within the draining lymph node and failure to produce anti-collagen IgG1 or IgG2a antibodies. To determine which CD28 ligand plays a more dominant role in CIA, we treated mice with monoclonal antibodies (mAb) against either B7-1 or B7-2. Neither anti-B7-1 nor anti-B7-2 had any effect on the course of CIA when given alone, but resulted in reduced incidence and clinical scores when given together. Interestingly, when treatment was delayed until after the onset of clinical disease, both CTLA-4Ig or anti-B7-1 plus anti-B7-2 mAb still ameliorated disease. Effective treatment was associated with a reduction in interferon-gamma production by lymph node cells following stimulation in vitro, suggesting that Th1 responses were diminished. This study points to a critical role of CD28 co-stimulation in the development and perpetuation of CIA in DBA/1 mice. Interestingly, it demonstrates an active role for T cells in the later stages of this disease and implicates both B7-1 and B7-2-mediated co-stimulation in the pathogenesis of CIA.